PENGARUH PENERAPAN TEKNOLOGI AI TERHADAP MAHASISWA DALAM PEMBELAJARAN AKUNTANSI DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Amanda, Ulya; Leli, Leli; Fahdah, Dina; Muchran, Muchriana (IJMA (Indonesian Journal of Management and Accounting), 2024)
The research aims to determine the effect of the application of Artificial Intelligence (AI) technology on students in accounting learning at the Universitas Muhammadiyah Makassar. The application of AI technology in accounting learning has the potential to change the way students learn, enrich their learning experiences, and improve their understanding of accounting materials. The variables in this study consist of the independent variable (application of AI technology) and the dependent variable (students in accounting learning). The type of research used is quantitative research with a survey method. The population in this study are all students of the Accounting study program at the Universitas Muhammadiyah Makassar. The sample will be determined using purposive sampling technique.So the research results show that the application of AI technology to Accounting learning has a significant effect, which means it has a positive effect on Accounting learning.